Cannabidiol Induces Autophagy to Protects Neural Cells From Mitochondrial Dysfunction by Upregulating SIRT1 to Inhibits NF-κB and NOTCH Pathways - Kang, Shaolei; Li, Jinglin; Yao, Zhihui; Liu, Jiaxin (Frontiers in Cellular Neuroscience, 2021)
The protective effect of Cannabidiol on Parkinson's (PD) has been found in recent study. However, the specific mechanism of the protective effect of Cannabidiol on PD nerve damage require further exploration. This study aims to investigate effect of Cannabidiol on MMP-induced Neural Cells (SH-SY5Y) mitochondrial dysfunction. MMP+ and Cannabidiol were used to treat SH-SY5Y cells, the cells viability was measured by MTT assay. The expression of Tyrosine hydroxylase (TH) in cells was measured by western blotting and Immunofluorescence staining. The relationship among Cannabidiol, Silent mating type information regulation 2 homolog- 1 (SIRT1) and NOTCH signaling, NF-κB signaling was examined by western blotting. The effect of Cannabidiol on MMP-induced mitochondrial dysfunction of SH-SY5Y cells was measured by western blotting. Cannabidiol alleviated loss of Tyrosine Hydroxylase expression and cytotoxicity in the MPP+-induced SH-SY5Y cells. Further mechanistic investigation showed that Cannabidiol induced SH-SY5Y cells autophagy to Protects Cells from Mitochondrial Dysfunction by up-regulating SIRT1 to Inhibits NF-κB and NOTCH Pathways. Taken together, Cannabidiol acts as a Protector in PD.